Aligning Fiqh Disaster with Indonesia’s Management Disaster Policy: A Maqāṣid Methodology Review - Arief, Ahmad; Sultan, Lomba; Amin, Abd. Rauf Muhammad; Musyahid, Achmad; Syarif, Muhammad Fazlurrahman (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
This study aims to align the principles of fiqh of disasters with Indonesia’s disaster management policies, particularly Law No. 24 of 2007. It seeks to explore how Islamic legal objectives can enrich and complement Indonesia's disaster governance framework. Using a maqāṣid based analytical approach, the research identifies and categorizes key elements within the maqāṣid framework, including concepts, objectives, values, societal groups, universal laws, divine commands, and textual evidences. These components are then systematically examined to evaluate their relevance and alignment with national disaster management strategies. The findings reveal a significant divergence in the interpretation of disaster and disaster management stakeholders between the two paradigms. Indonesian law defines disaster in technical-administrative terms, while fiqh emphasizes theological dimensions, such as divine awareness and submission to God’s will. Furthermore, the integration of religion as a vital element in disaster management remains insufficiently addressed in current policy frameworks. This study offers a novel integration of maqāṣid al-sharīʿah into the context of disaster management, proposing a theological-ethical dimension often overlooked in secular policy discourse. It bridges religious jurisprudence with contemporary disaster governance. The research suggests that involving religious leaders, institutions, and the Ministry of Religious Affairs in all disaster stages of prevention, response, and recovery can strengthen community resilience by fostering spiritual preparedness, psychological support, and culturally grounded disaster literacy.